2023
DOI: 10.4103/1673-5374.380821
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD36 in central nervous system diseases

Abstract: CD36 is a highly glycosylated integral membrane protein that belongs to the scavenger receptor class B family and regulates the pathological progress of metabolic diseases. CD36 was recently found to be widely expressed in various cell types in the nervous system, including endothelial cells, pericytes, astrocytes, and microglia. CD36 mediates a number of regulatory processes, such as endothelial dysfunction, oxidative stress, mitochondrial dysfunction, and inflammatory responses, which are involved in many ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 132 publications
1
2
0
Order By: Relevance
“…This is in alignment with Scott et al‘s findings, which indicated enhanced neurological recovery in CD36 knockout mice following spinal cord injury [ 48 ]. CD36 is predominantly expressed in microglia and astrocytes within the brain [ 49 ], as confirmed by our experiments, and is known to modulate inflammatory responses and glial scarring [ 44 , 45 , 50 , 51 ]. Furthermore, CD36 expression in vascular endothelial cells has been implicated in fatty acid transport [ 52 ] and the regulation of angiogenesis [ 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…This is in alignment with Scott et al‘s findings, which indicated enhanced neurological recovery in CD36 knockout mice following spinal cord injury [ 48 ]. CD36 is predominantly expressed in microglia and astrocytes within the brain [ 49 ], as confirmed by our experiments, and is known to modulate inflammatory responses and glial scarring [ 44 , 45 , 50 , 51 ]. Furthermore, CD36 expression in vascular endothelial cells has been implicated in fatty acid transport [ 52 ] and the regulation of angiogenesis [ 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…The emphasis is on the fatty acid transport function of CD36 within the cardiovascular system, as it has been most extensively studied in this context. We do not discuss the role of CD36 in other tissues but refer the reader to more comprehensive reviews on CD36 in platelet biology (8), in atherosclerosis (9,10), in intestine (11), in liver and nonalcoholic fatty liver disease (12,13), in the central nervous system (14), and in cancer (15)(16)(17)(18)(19).…”
Section: Clinical Highlightsmentioning
confidence: 99%
“…Numerous life-threatening diseases demand the advancement of efficient, reliable, and noninvasive methods for early diagnosis and the precise identification of key biomarkers such as those embodied within small extracellular vesicles (sEVs) [1][2][3]. Surface-enhanced Raman spectroscopy (SERS) has emerged as a powerful technique for biosensing applications, leveraging the plasmonic resonance of metallic nanostructures such as gold and silver.…”
Section: Introductionmentioning
confidence: 99%